Sunburn disorder in tropical and subtropical fruits. A review - Fischer, Gerhard; Orduz-Rodríguez, Javier Orlando; Amarante, Cassandro Vidal Talamini do (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2022)
The increase in solar radiation and temperature as a result of climate change and variability has increased sunburn damage to fruits, which highly affects quality and yield in tropical and subtropical fruit plants. Solar injuries increase because of conditions with low relative humidity, fruits left uncovered by foliage, and plantations at higher altitudes as a result of increased UV radiation. Three different types of sunburn on fruits are distinguished: photooxidative sunburn, sunburn browning, and necrosis on the epidermis. Fruits employ self-protection mechanisms against this stress through the production of enzymatic and non-enzymatic antioxidants. Fruit growers try to mitigate the impact of sunburning by planting species and varieties that are tolerant to this stress, pruning and training plants, leaving enough leaves above the fruit, efficient irrigation and intercropping for shading. More technical sunburn mitigation strategies include 1) improving the microclimate (shading nets, fruit bagging, evaporative cooling), 2) suppressors (kaolinite clay particle films, calcium carbonate) or 3) chemical protection (tocopherol, abscisic acid, ascorbic acid, anti-transpirants). This paper presents the state of research and its results for this abiotic stress in some tropical and subtropical fruit trees, such as avocado, banana, citrus, mango, pineapple and pitaya, along with observations for other fruit trees in tropical altitude zones. Continued research is recommended for this stress in different varieties with the use of environmentally friendly protective materials, along with studies on molecular mechanisms that direct the acclimatization of plants to a combination of these two types of stress, excessive radiation and temperature.